Koreografi Tari Sentak Ilau di Sanggar Seni Nan Gombang Painan Kabupaten Pesisir Selatan - Dyvia Allisa; Venny Rosalina (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This study aims to reveal, describe and analyze the Choreography of Sentak Ilau Dance at Nan Gombang Painan Art Center, South Pesisir Regency. This type of research is qualitative research using descriptive methods. This research instrument is the researcher himself assisted by supporting instruments in the form of stationery and cameras. Data were collected through literature study, observation, interviews and documentation. The steps of analyzing data are data collection, data reduction, data presentation and conclusions. The results of this study show that the choreography form of Sentak Ilau Dance at Nan Gombang Painan Art Studio in South Pesisir Regency consists of Motion, Top Design, Dynamics, Dramatic Design, Floor Design, Costumes, Properties, Group Composition, and Dance Accompaniment. Sentak Ilau Dance movement comes from Silek Tiger dance, Rantak Kudo and Salido cloth. The top design of Sentak Ilau Dance consists of Angular, Curved, High, Low, Flat, Vertical, Horizontal, Medium and contrasting top designs. The dynamics of Sentak Ilau Dance consists of three aspects, namely aspects of space, time and energy. The dramatic atmosphere in the dance is divided into 2 parts, namely calm and tense. The floor design used varies. Sentak Ilau's dance floor design consists of straight and curved lines. The musical instruments used are such as violin, kompang, bansi, serunai, saluang, talempong and tamburin. The property used in this sentak ilau dance is a jug containing frankincense and used tin bottles containing small stones. The costumes used are modified costumes, namely modified kuruang basiba clothes, Galembong, Saspayang cloth, headdresses used from sisampiang cloth and belts.